Motives Linking Subclinical Psychopathy and Benign Masochism to Recreational Drug use - Sagioglou, Christina (Journal of drug issues, 2024)
As the use of some psychoactive substances continues to be a global health risk, it is important to understand why people use them. We compared the predictive power of psychopathy and masochism with regard to lifetime recreational drug use and tested the underlying motives in a sample of 415 US-based adults. Psychopathy predicted use of illicit drugs, cannabis, and nicotine, while masochism predicted cannabis, alcohol, and caffeine use. Both traits were related to most motives, but the motives differentially predicted substance use. Expansion motivation was the sole motive for illicit drug use, whereas cannabis was predicted mainly by expansion and enhancement. Alcohol, nicotine, and caffeine were used to escape daily worries, and alcohol was further used for social reasons. Benign masochism is a newly identified predictor of popular drug use. Future research could investigate masochism and expansion motivation as predictors of potentially harmful substance use.